Amorphous Cu-added/SnOx/CNFs composite webs as anode materials with superior lithium-ion storage capability1. Issue 51 (5th June 2015) - Chi, Cheng; Lan, Jinle; Sun, Jiangman; Liu, Yuan; Yu, Yunhua; Yang, Xiaoping
<x xml:space="preserve">Abstract</x> Cu-addition plays a significant role in restricting the aggregation of Sn particles during a continuous charge–discharge progress and improving the cycling stability of SnOx/CNFs electrode.